The Role of the SDR in the International Monetary System - Roushdy, Juanita (Occasional Papers; Occasional Paper ;, 1987)
In the years since the SDR was created, the international monetary system has experienced a number of profound changes. The present paper sketches the effects of these changes on perceptions of the role that the SDR can and should play in that system.